Characterization of Basement Fracture Reservoir In Field âXâ, South Sumatera Basin, Based On The Analysis of Core And FMI Log - Riskha, Hartawi; Syafri, Ildrem; Ismawan, Ismawan; Natasia, Nanda (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Basement reservoir is a reservoir that is located in the basement rock, comprised of either igneous rock or metamorphic rock that has secondary porosity, resulting in its capability to store oil and gas. The research was conducted at field X that is located at South Sumatra basin and it is a part of Jambi Sub-Basin. The study was focused on discussing hydrocarbon potential in Fields X, particularly at the basement metamorphic rock. The study was conducted at two wells in the field. The secondary porosity system of the basement is fracture porosity. Fracture analysis as secondary porosity system was performed on two wells, HA-1 and HA-2, by using FMI log interpretation. Based on the analysis of fracture on HA-1 well, the trend of fracture system is Northeast - Southwest (NE-SW) with a fracture porosity of 1.49%. On a different note, the trend of fracture system on HA-2 wells is East Northeast - West Southwest (ENE-WSW) with a fracture porosity of 0.888%. The effect of rock properties itself has little influence on the number of fractures as opposed to the effect of surrounding tectonic forces. The fractures are controlled by geological structures following Jambi pattern that has an orientation of Northeast - Southwest (NE-SW). Although the fracture porosity is relatively small, it is enough to storing hydrocarbons in economical quantity.